2012
DOI: 10.1080/13811118.2013.722057
|View full text |Cite
|
Sign up to set email alerts
|

A Trait-Interpersonal Perspective on Suicide Risk in Criminal Offenders

Abstract: Despite elevated rates of suicide among offenders, research has yet to adequately address theoretically driven risk models in this population. The present study addresses such a gap by investigating a synthesized framework using 2 well-developed theoretical models, the Five-Factor Model (FFM) of personality and the interpersonal-psychological theory of suicide (IPTS). Archival data from mitigation evaluations for pre-sentenced criminal offenders (n = 307) were analyzed using structural equation modeling (SEM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 35 publications
5
38
3
Order By: Relevance
“…Among 306 criminal offenders Cramer (2012) found that introversion predicted interpersonal-psychological theory of suicide (IPTS) components of burdensomeness, thwarted belongingness, and acquired capability. Low resilience on the CD-RISC, as found here, has also been found to be associated with suicide attempts in depressed patients and resilience may be a protective factor mitigating the risk of suicidal behavior associated with childhood trauma (Roy, Carli, & Sarchiapone, 2011;Roy, Sarchiapone, & Carli, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among 306 criminal offenders Cramer (2012) found that introversion predicted interpersonal-psychological theory of suicide (IPTS) components of burdensomeness, thwarted belongingness, and acquired capability. Low resilience on the CD-RISC, as found here, has also been found to be associated with suicide attempts in depressed patients and resilience may be a protective factor mitigating the risk of suicidal behavior associated with childhood trauma (Roy, Carli, & Sarchiapone, 2011;Roy, Sarchiapone, & Carli, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As aspects of the IPTS are both environmentally and biologically influenced (Van Orden et al., ), it stands to reason that personality traits (biological predispositions) may influence the manifestation of such constructs. Indeed, cross‐sectional empirical findings suggest that traits such as neuroticism are related to IPTS constructs (e.g., Cramer et al., ), suggesting the potential utility of a trait‐interpersonal perspective of suicide in furthering understanding of suicide proneness among sexual minorities.…”
Section: The Iptsmentioning
confidence: 99%
“…Cramer et al. () addressed several of the limitations (specifically, integrated FFM–IPTS pathways and analysis of suicide‐related constructs) in a sample of Australian male offenders. The basic assumption of the trait‐interpersonal approach they employed is that, consistent with FFM theory (Costa & McCrae, ), personality traits impact, or contribute to, the presence or formation of IPTS constructs, which in turn lead to suicidal ideation and proneness.…”
Section: The Present Study: Application Of a Trait‐interpersonal Persmentioning
confidence: 99%
“…Identifying offenders with high physiological anxiety may also be helpful due to the increased levels of suicidal ideations associated with physiological anxiety, as demonstrated in the current study. In light of burgeoning literature on scales demonstrating value in offender populations (e.g., Cramer et al, 2012;Wang et al, 1997), it is plausible that the LSRP and PAI may be useful screening tools for suicide risk assessment with offenders. However, more research is needed in this area to fully validate these instruments for such purposes.…”
mentioning
confidence: 99%
“…Moreover, suicide assessment still merits attention in nonclinical PREDICTORS OF SUICIDAL IDEATION IN OFFENDERS samples. For example, preincarcerated offenders (Cramer et al, 2012), college students (Cukrowicz, Smith, Hohmeister, & Joiner, 2009), and the elderly (Rocco, Orbitello, Ciano, Angarano, & Balestrieri, 2004) all have an elevated risk for suicide.…”
mentioning
confidence: 99%